(untitled) (Acta Entomologica Serbica, 2016)
Although the Vlasina plateau has proved to be an interesting area hosting diverse and unique flora and fauna, itsbutterflies have not been thoroughly studied. Consolidating several known records and our field observations, a total of101 butterfly species were listed for this region. The area hosts a number of important species to be conserved underNatura 2000 and Emerald networks and a significant number of nationally important species. The most interesting recordis Colias caucasica, a butterfly not yet recorded in the neighboring region, and its finding is described here in more detail.